Kickstarting Immunity in Cold Tumours: Localised Tumour Therapy Combinations With Immune Checkpoint Blockade - Appleton, Elizabeth; Hassan, Jehanne; Chan Wah Hak, Charleen; Sivamanoharan, Nanna; Wilkins, Anna; Samson, Adel; Ono, Masahiro; Harrington, Kevin J.; Melcher, Alan; Wennerberg, Erik (Frontiers in Immunology, 2021)
Cancer patients with low or absent pre-existing anti-tumour immunity (“cold” tumours) respond poorly to treatment with immune checkpoint inhibitors (ICPI). In order to render these patients susceptible to ICPI, initiation of de novo tumour-targeted immune responses is required. This involves triggering of inflammatory signalling, innate immune activation including recruitment and stimulation of dendritic cells (DCs), and ultimately priming of tumour-specific T cells. The ability of tumour localised therapies to trigger these pathways and act as in situ tumour vaccines is being increasingly explored, with the aspiration of developing combination strategies with ICPI that could generate long-lasting responses. In this effort, it is crucial to consider how therapy-induced changes in the tumour microenvironment (TME) act both as immune stimulants but also, in some cases, exacerbate immune resistance mechanisms. Increasingly refined immune monitoring in pre-clinical studies and analysis of on-treatment biopsies from clinical trials have provided insight into therapy-induced biomarkers of response, as well as actionable targets for optimal synergy between localised therapies and ICB. Here, we review studies on the immunomodulatory effects of novel and experimental localised therapies, as well as the re-evaluation of established therapies, such as radiotherapy, as immune adjuvants with a focus on ICPI combinations.